The Impact of E-Procurement on the Number of Suppliers: Where to Move to? - Daniel Nepelski (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
This paper examines how electronic procurement influences the organization of economic transactions. It seeks evidence for ICT-induced changes in how companies organize their activities and whether ICT lead to more competitive and transparent markets. Testing the relationship between the effect of electronic procurement on procurement cost and sourcing strategy, I provide new evidence that electronic procurement leads to more market transactions. This leads to the conclusion that electronic procurement increases market transparency, lowers search and supplier switching costs and improves the management of supply chain and contradicts the predictions that ICT will lead to a dominance of network-like organizational form and an increasing reliance on hybrid forms of organizing economic transactions. Two implications emerge from these results. The first one is relevant for companies engaging in ICT projects. ICT combined with changes in business strategy leads to a reduction of market transaction costs and, as a result, opens up new possibilities in terms of how business activities can be organized and/or how to structure competition in upstream markets. This effect of new technologies is of clear benefit to companies successfully implementing and using new technologies. The second implication is of great importance for companies whose customers implement ICT to intensify competition among suppliers. Changing environment forces them to adapt to new market conditions and look for new ways of maintaining profitability.
Keywords: L22; 330; information technology and firm boundaries; markets vs. hierarchies; sourcing strategy; electronic procurement